Polyethylene Glycol Loxenatide Injection (GLP-1) Protects Vascular Endothelial Cell Function in Middle-Aged and Elderly Patients With Type 2 Diabetes by Regulating Gut Microbiota - Chen, Fengwu; He, Lina; Li, Jilin; Yang, Shuhui; Zhang, Bangzhou; Zhu, Dan; Wu, Zezhen; Zhang, Shuo; Hou, Ducheng; Ouyang, Cong; Yi, Jianfeng; Xiao, Chuanxing; et al. (Frontiers in Molecular Biosciences, 2022)
Objective: To evaluate the protective effect of Polyethylene Glycol Loxenatide Injection (Glucagon-like peptide-1,GLP-1) on endothelial cells from middle-aged and elderly patients with newly diagnosed or poorly controlled type 2 diabetes mellitus(T2DM). GLP-1 weekly formulation was analyzed for cardiovascular disease protection and correlated with intestinal flora. Design:Stool samples were collected from middle-aged and elderly patients with new-onset or poorly controlled type 2 diabetes in Longhu People’s Hospital and Shantou Central Hospital from June 2019 to November 2019. Samples were collected at week 0 , 4 and 8 of treatment with GLP-1 weekly formulations. Samples were analyzed for metagenomic sequencing. Analysis was performed to compare the characteristics of the gut microbiota at week 0, 4 and 8 of GLP-1 treatment and to correlate different microbiota with characteristic clinical parameters. Results:Statistical differences were found in blood glucose lowering, cardiovascular endothelial, and inflammation-related indices between week 0 and W4 and in blood glucose lowering and cardiovascular endothelial indices from week 0 to 8 in the newly diagnosed or poorly controlled type 2 diabetic patients treated with GLP-1. Changes in gut microbiota at week 0, 4, and 8 after using GLP-1 were not statistically different, but had an overall trend of rising and then falling, and with different bacteria, that were correlated with different clinical indicators . Conclusion:GLP-1 improves endothelial cell function indicators in middle-aged and elderly diabetic patients, which may be related to its alteration of the population numbers of gut microbiota such as Acinetobacter, Eubacterium ramulus ATCC 29099 and Bacteroides_faecis. This study provides a guidance for the treatment of type 2 diabetic patients.